Selective Cobalt-Catalyzed Reduction of Terminal Alkenes and Alkynes Using (EtO)(2)Si(Me)H as a Stoichiometric Reductant - Raya, Balaram (ACS Catal, 2016)
While attempting to effect Co-catalyzed hydrosilylation of β-vinyl trimethylsilyl enol ethers we discovered that depending on the silane, solvent and the method of generation of the reduced cobalt catalyst, a highly efficient and selective reduction or hydrosilylation of an alkene can be achieved. This paper deals with this reduction reaction, which has not been reported before in spite of the huge research activity in this area. The reaction, which uses an air-stable [2,6-di(aryliminoyl)pyridine)]CoCl(2) activated by 2 equivalents of NaEt(3)BH as a catalyst (0.001–0.05 equiv) and (EtO)(2)SiMeH as the hydrogen source, is best run at ambient temperature in toluene and is highly selective for the reduction of simple unsubstituted 1-alkenes and the terminal double bonds in 1,3- and 1,4-dienes, β-vinyl ketones and silyloxy dienes. The reaction is tolerant of various functional groups such as a bromide, alcohol, amine, carbonyl, and di or trisubstituted double bonds, and water. Highly selective reduction of a terminal alkyne to either an alkene or alkane can be accomplished by using stoichiometric amounts of the silane. Preliminary mechanistic studies indicate that the reaction is stoichiometric in the silane and both hydrogens in the product come from the silane.